20.4k views
5 votes
Please help ASAP !!!

Please help ASAP !!!-example-1

2 Answers

6 votes

Answer:

The solution of above equation is x = 3.

Explanation:

We have given a quadratic equation.

2x-3 = x²/3

We have to find the value of x.

Multiplying both sides of given equation by 3, we have

3(2x-3) = 3(x²/3)

6x-9 = x²

Simplifying above equation,we have

x²-6x+9 = 0

Splitting the middle term of above equation, we have

x²-3x-3x+9 = 0

Making groups , we have

x(x-3)-3(x-3) = 0

Taking (x-3) as common, we have

(x-3)(x-3) = 0

Applying Zero-Product Property to above equation, we have

x-3 = 0 or x-3 = 0

x = 3 or x = 3

Hence,The solution of above equation is x = 3.

User Vinay B R
by
5.5k points
3 votes

Answer: x=3

Explanation:

To solve this problem you must apply the proccedure shown below:

- Multiply both sides of the equation by 3:


3(2x-3)=3((x^2)/(3))\\6x-9=x^(2)

- Now you must make the equation equal to zero as following:


6x-9=x^(2)\\x^(2)-6x+9=0

- Factor it, as you can see below. Therefore, you obtain the following result:


(x-3)(x-3)=0\\(x-3)^2=0\\x=3

User Ronser
by
5.6k points